Digitalization of Sharia Investment: The Contribution of Investment Platforms to Sharia Capital Market Literacy and Inclusion - Siti Nur Azizah; Ismatul Khayati (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study was motivated by the rapid digitalization that has brought significant changes to the financial sector, particularly the Islamic capital market. Although the number of investors has increased, the level of literacy (43.42%) and Islamic financial inclusion (13.41%) remain low. This study aims to analyze the contribution of digital investment platforms in improving literacy and inclusion in the Islamic capital market in Indonesia. The method used is qualitative with a literature study, based on secondary data from journals, books, official reports, and related publications. The results show that digital platforms such as Bibit, Bareksa, IPOT, and Ajaib not only serve as a means of transaction but also as a medium of education through literacy programs, collaboration, and transparency and security features. Digitalization has been proven to reduce barriers to participation, provide cost efficiency, and expand investment access, especially for the younger generation.